Facts About Citrus Fruits and Juices: Grapefruit - Gail C. Rampersaud (EDIS, 2002)
This document is FSHN026, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: September 2002.